Fungal Endophytic Beauveria bassiana in Chinese Kale Against Plutella xylostella (L.) Larvae - Afandhi, Aminudin; Ikawati, Silvi; Baroro, Ismatul; Afiyanti, Mufidah; Sari, Rose Novita; Handoko, Handoko; Suyono, Tri; Setiawan, Yogo; Tarno, Hagus (Research Journal of Life Science, 2021)
This study evaluated three methods of inoculation of Beauveria bassiana endophytes from Chinese kale and then infected into Plutella xylostella L to determine the mortality rate. The endophytic B. bassiana using three different inoculation methods including seeds-soaking, leaf-spraying, and soil-wetting. The Chinese kale seeds from Winsa variety, B.bassiana isolates derived from collection planthopper. The endophytic fungus was identified to be B. bassiana based on the analysis of colony morphology. The results of this study included the degree of colonization of Chinese kale plants and the mortality of P. xylostella. The average B. bassiana colonies in leaves were 13.89%, stems 2.77% and roots 5.55%. The results showed on leaves that the seeds-soaking method obtained higher colonization of B. bassiana rate when compared to leaf-spraying and soil-wetting. The highest percentage of P. xylostella mortality was generated from seeds-soaking (45%), soil-wetting (37.5%), leaf-spraying (35%). The B. bassiana fungus which caused the fastest LT50 with a seeds-soaking (409.48 hours), and then soil-wetting (679.15 hours), leaf-spraying (1090.21 hours). The positive effects of seeds-soaking of endophytic B. bassiana and mortality of Plutella xylostell.